Enzymology of Bacterial Lysine Biosynthesis - Dogovski, Con; Atkinson, Sarah. C.; Dommaraju, Sudhir R.; Downton, Matthew; Hor, Lilian; Moore, Stephen; Paxman, Jason J.; Peverelli, Martin G.; Qiu, Theresa W.; Reumann, Matthias; Siddiqui, Tanzeela; Taylor, Nicole L.; et al. (IntechOpen, 2012)
None